(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study aimed to know the degree to which directors of the northeastern Badia schools in Jordan practice electronic management in distance education during the Corona pandemic from their point of view, and to identify the impact of each of the sex, academic qualification, and experience in that. All school principals and principals have been selected, consisting of (148 (Director and Director of NARA) due to the small size of the study population, and his questionnaire was used to measure the degree of electronic management practice, and its validity and reliability were ascertained, and the results showed that the degree of practice of the degree of practice of the principals of the Northeastern Badia Schools of electronic management in distance education during the Corona pandemic, from their point of view, was moderate. On the tool as a whole and in the fields of electronic planning and electronic communication, while it came with a high degree in the field of supporting learning methods. The results showed that there were no statistically significant differences due to the effect of gender, educational qualification, and years of experience in all fields.